Analysis of the Effect of Load Variations on Generator Efficiency at the Sarulla Operations Ltd. Geothermal Power Plant - Samosir, Sarah Suharni (Universitas Muhammadiyah Ponorogo, 2024)
This research aims to analyze the influence of steam flow rate values on generator input power and the influence of generator load variations on generator efficiency. PLTP is a power plant whose energy source comes from geothermal energy which is converted into electrical energy. Sarulla Operations Ltd. is one of the GPPs in Indonesia with a total installed capacity of 330 MW, located in North Sumatra Province. The generator is one of the main components used to convert mechanical energy from the steam turbine into electrical energy. The problem that is often encountered with generators is instability of generator efficiency. The method used in this research is a descriptive method with a quantitative approach. This research was carried out at the STG unit which applies single flash steam technology at the Sarulla PLTP NIL 2 unit, where the generator load value according to specifications is 57.45 MW. The research data analyzed was taken from data from Friday, 01 December to Tuesday, 05 December 2023 at 07.00, 11.00, 15.00, 19.00 and 23.00 WIB. The results of the first research show that when the maximum steam flow rate value is 185.84 kg/s, the generator input power is 62.54 MW and when the minimum steam flow rate value is 153.67 kg/s, the generator input power is 54.35 MW. The results of the second research show that when the maximum generator load value is 59.22 MW, the generator efficiency is 94.70% and when the minimum generator load value is 46.31 MW, the generator efficiency is 85.20%. The higher the steam flow rate value, the higher the generator input power and the higher the generator load value, the higher the generator efficiency obtained.